At the table of power : food and cuisine in the African American struggle for freedom, justice, and equality - Spivey, Diane M., 1949- (University of Pittsburgh Press, 2022)
"At the Table of Power is both a cookbook and a culinary history that intertwines social issues, personal stories, and political commentary. Renowned culinary historian Diane M. Spivey offers a unique insight into the historical experience and cultural values of African America and America in general by way of the kitchen. From the rural country kitchen and steamboat floating palaces to marketplace street vendors and restaurants in urban hubs of business and finance, Africans in America cooked their way to positions of distinct superiority, and thereby indispensability. Despite their many culinary accomplishments, most Black culinary artists have been made invisible--until now. Within these pages, Spivey tells a powerful story beckoning and daring the reader to witness this culinary, cultural, and political journey taken hand in hand with the fight of Africans in America during the foundation years, from colonial slavery through the Reconstruction era. These narratives, together with the recipes from the nineteenth and twentieth centuries, expose the politics of the day and offer insight on the politics of today. African American culinary artists, Spivey concludes, have more than earned a rightful place at the table of culinary contribution and power."--